Peran suami terhadap penanganan baby blues pada wanita postpartum - Falahurrofiqo, Falahurrofiqo; Ardani, Tristiadi Ardi (Maliki Interdisciplinary Journal, 2024)
Postpartum women will experience drastic changes, both physical and psychological. The drastic changes he experiences put him in trouble, which can cause baby blues syndrome or even postpartum depression. The husband's support, including social integration, words of comfort, reliable support, and guidance, plays an important role in reducing the wife's psychological burden. Husbands who understand their wives' needs after giving birth can strengthen the relationship between husband and wife and help wives adapt after giving birth. Social support, especially from the husband, has a positive impact in preventing baby blues and postpartum depression. In conclusion, the husband's role in providing psychological support to his wife postpartum is very important for the mental and emotional well-being of the family.